ASPECTS OF MORPHOGENETIC TRAITS ASSOCIATED WITH PHYSIOLOGICAL COEFFICIENTS RELATED TO INCIDENCE OF OBESITY, HYPERTENSION, AND DIABETES MELLITUS - ONWUKA, OSAH MARTINS; NWOSU, NKECHI CLARA; OKERULU, ADAOBI LINDA; CHUKWUEMEKA AJUZIE, GODSON (Innovare Journal of Life Sciences, 2023)
The vulnerability to develop certain pathophysiological conditions may be linked to the morphogenetic traits of individuals. Hence, this study ascertained the relationship between some morphogenetic traits and physiological coefficients related to incidence of obesity, hypertension, and diabetes mellitus. Morphogenetic traits (height, weight, ABO blood group, Hitchhiker thumb, tongue rolling, and hand clasping) and physiological coefficients; body mass index, blood pressure (BP), random blood sugar (RBS), and fasting blood sugar (FBS) were measured during a free medical outreach in an institution in Eastern Nigeria. Seventy individuals participated; age (15–35 years), females: 36 (51.4%), males: 34 (48.6%), pre-obese (28.6%), obese 1 and 2 (2.9%, 2.9%), and BP (52.9% normal and 34.3% hypotensive). Twenty-five (35.7%) assayed FBS showed 1.4% diabetes, 17.1% pre-diabetes, and 17.1% normal, while 45 (64.3%) assayed RBS showed 57.1% normal and 7.2% pre-diabetes. There was significantly increased incidence of pre-diabetes and diabetes among tongue rollers when compared to non-tongue rollers (p<0.05). Incidence of obesity and hypertension was not significantly associated with tongue rolling. There was significant association between weight and incidence of obesity (p<0.05); no significant association with weight and incidence of hypertension and diabetes. There was also no association between height, ABO blood group, Hitchhiker thumb, hand clasping and incidence of obesity, hypertension, and diabetes (p<0.05). Conclusively, morphogenetic traits such as tongue rolling and body weight were associated with physiological coefficients related to incidence of diabetes and obesity, respectively, supporting the hypothesis that certain morphogenetic traits can be linked to the proneness of individuals to obesity and diabetes.